Landscape-Mediated Edge Effect in Temperate Deciduous Forest: Implications for Oak Regeneration - Vergara-Egert, P (Springer Netherlands, 2019)
Context: Although the edge effect is known to be an important factor influencing the recruitment of trees in temperate forests, little is known of its synergistic relationships with landscape and fragment attributes. Objectives: We investigated how the edge effect on regeneration of oaks (Quercus spp.) varies with respect to fragment geometry, connectivity and landscape composition. Methods: We recorded oak sapling density along edge-interior gradients in 29 forest fragments at the periphery of Mexico City and examined the data with Generalized Additive Models. Results: A nonlinear and landscape-mediated edge effect was supported by data, including the interactions of the edge distance with patch connectivity, shape and size. Saplings were more abundant at a distance of ca. 50 m from the edge of small, large and connected patches, but large patches also exhibited reduced recruitment towards the interior of the patch. Conversely, sapling density in simple-shaped or connected patches was lower at the edge, exhibiting linear and concave-down increase trends towards the interior of patches, respectively. Conclusions: Boundary conditions could be interacting with interior forest conditions, making regeneration more frequent at 50 m from the edge. Shady and cooler sites in large patches may be inhibiting oak regeneration. The activity of acorn-dispersing animals and oak predators may increase in unconnected patches, thus increasing the likelihood of edge effects. These results provide insights into the restoration of temperate forest patches in heterogeneous fragmented landscapes. © 2018, Springer Nature B.V.